2016
DOI: 10.7717/peerj.1890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poly (ADP-ribose) polymerase-1 (PARP-1) inhibition on sulfur mustard-induced cutaneous injuriesin vitroandin vivo

Abstract: Early studies with first-generation poly (ADP-ribose) polymerase (PARP) inhibitors have already indicated some therapeutic potential for sulfur mustard (SM) injuries. The available novel and more potential PARP inhibitors, which are undergoing clinical trials as drugs for cancer treatment, bring it back to the centre of interest. However, the role of PARP-1 in SM-induced injury is not fully understood. In this study, we selected a high potent specific PARP inhibitor ABT-888 as an example to investigate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…In the present study, it was also identified that down-expression of PARP-1 (via olaparib) significantly decreased the cellular viability of PanC-1 cells, increased p53 protein expression, decreased expression of pro-caspase-3, increased caspase-3 activity and suppressed Bcl-2 protein expression following the inhibition of ATM activity. Liu et al (24) reported that PARP had an effect on sulfur mustard-induced cutaneous injuries in vitro and in vivo via the caspase-3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was also identified that down-expression of PARP-1 (via olaparib) significantly decreased the cellular viability of PanC-1 cells, increased p53 protein expression, decreased expression of pro-caspase-3, increased caspase-3 activity and suppressed Bcl-2 protein expression following the inhibition of ATM activity. Liu et al (24) reported that PARP had an effect on sulfur mustard-induced cutaneous injuries in vitro and in vivo via the caspase-3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in models of sulfur mustard induced dermatitis, the beneficial effects of the PARP inhibitor ABT-88, as well as the beneficial effects of PARP1 deficiency, appears to involve a significant modulation of the Akt pathway. In these experiments, sulfur mustard exposure decreased Akt phosphorylation in the control group, while in the PARP1/deficiency + sulfur mustard groups, a marked increase in Akt phosphorylation was observed [65].…”
Section: Role Of the Parp-akt Interplay In Shock And Inflammationmentioning
confidence: 64%
“…Despite the exhaustive number of studies on the secretion of TGF-β by human MSCs [24], no study was found examining the secretion of TGF-β by these cells in normal and preeclamptic pregnancies. Eng-1 increased, and concluded that this change could be associated with the severity of disease [25]. On the other hand, by measuring the plasma level of TGF-β in the third trimester of pregnancy, Paracoli et al showed that the level of this factor increased significantly in PE as compared with that in normal pregnancy demonstrating that changes in this factor shows its involvement in the pathophysiology of the disease [26].…”
Section: Discussionmentioning
confidence: 99%